Foreign direct investment, spillovers and absorptive capacity: Evidence from quantile regressions - Sourafel Girma; Holger Görg (Kiel Institute for World Economics (IfW), 2005)
This paper focuses on the role of absorptive capacity in determining whether or not domestic firms benefit from productivity spillovers from FDI using establishment level data for the UK. We allow for different effects of FDI on establishments located at different quantiles of the productivity distribution by using conditional quantile regression. Overall, while there is some heterogeneity in results across sectors and quantiles, our findings clearly suggest that absorptive capacity matters for productivity spillover benefits. We find evidence for a u-shaped relationship between productivity growth and FDI interacted with absorptive capacity. We also analyse in some detail the impact of changes in absorptive capacity on establishments' ability to benefit from spillovers.
Keywords: F21; F23; 330; Absorptive capacity; Productivity spillovers; Quantile regressions; Foreign direct investment; Produktivität; Eigentümerstruktur; Multinationales Unternehmen; Spillover-Effekt; Elektronikindustrie; Feinmechanische Industrie; Schätzung; Großbritannien